Verification Method for Analysis of Iron (Fe) in Water Irrigation at Sukarame, South Lampung Using Atomic Absorption Spectrophotometry - Ayu Rahayu Saraswati; Nurbaiti; Ulfah Izdihar; Melysa Saleh (Agriwar Journal, 2025)
The concentration of iron (Fe) in irrigation water is crucial due to its potential impact on the safety of agricultural products. This study verified the Atomic Absorption Spectrophotometry (AAS) method for analyzing Fe levels in irrigation water in Sukarame, South Lampung. AAS was chosen for its sensitivity, selectivity, and multi-element analysis capabilities. The verification process included preparing Fe standard solutions, determining the limit of detection (LOD) to assess sensitivity, and evaluating accuracy and precision through repeated measurements of irrigation water samples. Results demonstrated excellent linearity of the standard curve (R² = 0.9985). The achieved LOD of 0.0467 mg/L indicated high sensitivity. Accuracy and precision analyses revealed dissolved Fe levels of 2.549 mg/L and total Fe levels of 11.006 mg/L. Both dissolved, and total Fe concentrations were below the established irrigation water quality standard of 5 mg/L for dissolved Fe. This verification confirms the suitability of the AAS method for routine monitoring of Fe in irrigation water in the Sukarame region, ensuring the safety and quality of agricultural produce.